2019
DOI: 10.1097/aln.0000000000002813
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Penetrance and Clinical Expression of Malignant Hyperthermia in Individuals Carrying Diagnostic Ryanodine Receptor 1 Gene Mutations

Abstract: M alignant hyperthermia (MH) is a rare life-threatening disorder caused by dysregulation of intracellular calcium homeostasis in skeletal muscle and triggered by exposure to certain anesthetics in genetically predisposed individuals. 1 A progressively better understanding of the pathomechanism of MH, advances in anesthesia monitoring, and the introduction of dantrolene have been crucial in reducing MH mortality, which remains around 10%. 2 Variants in ryanodine receptor 1 (RYR1), 3 calcium voltage-gated channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
(47 reference statements)
3
38
1
Order By: Relevance
“…We conducted a retrospective cohort study and a systematic review to provide an up-to-date, comprehensive summary of the documented cases. As anticipated from previous reports 7,41,89 , we found that young age and male gender are significant risk factors for heat-sensitivity among individuals with RYR1 variants associated with MHS. Children with MHS, especially infants, are the most vulnerable to heat-induced death.…”
Section: Discussionsupporting
confidence: 89%
“…We conducted a retrospective cohort study and a systematic review to provide an up-to-date, comprehensive summary of the documented cases. As anticipated from previous reports 7,41,89 , we found that young age and male gender are significant risk factors for heat-sensitivity among individuals with RYR1 variants associated with MHS. Children with MHS, especially infants, are the most vulnerable to heat-induced death.…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that prevalence or susceptibility to MH is increased in male humans 35,36 and mice 37 . Furthermore, it has been reported that odds of developing MH are greater in males than females even with similar exposures to anesthetics 7 . Our study also shows that energy expenditure, at temperatures that do not trigger MH, is influenced by sex with differences between HET and WT mice restricted to male animals.…”
Section: Discussionsupporting
confidence: 59%
“…This energetic crisis can be triggered by volatile anesthetics, depolarizing muscle relaxants (eg, succinylcholine), intense exercise, and exposure to elevated environmental temperatures 5 . The prevalence in the human population of known MH‐causative mutations is 1:2750, 6 with variants in the ryanodine receptor 1 gene ( RYR1 ) being responsible for the majority of MH cases 7 . Polymorphism and expressed variants within the RYR1 gene have been estimated to occur in greater than 50% of people from MH‐susceptible families, although it remains unclear how many of these confer pathogenic risks 6,8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Incomplete penetrance affecting the expression of PSS has previously been observed in pigs (Ollivier et al, 1975;Smith & Bampton, 1978). In humans, penetrance in expression of the afflicted condition resulting from mutations in RYR1 was significantly greater in males than in females (50% versus 30%; P =0.002), despite similar levels of exposure to trigger anaesthetics (Ibarra Moreno et al, 2019).…”
Section: Tablementioning
confidence: 96%